Leaky Integrate‐and‐Fire Mechanism in Exciton–Polariton Condensates for Photonic Spiking Neurons. Issue 1 (30th September 2022) - Tyszka, Krzysztof; Furman, Magdalena; Mirek, Rafał; Król, Mateusz; Opala, Andrzej; Seredyński, Bartłomiej; Suffczyński, Jan; Pacuski, Wojciech; Matuszewski, Michał; Szczytko, Jacek; Piętka, Barbara
Abstract: This paper introduces a new approach to neuromorphic photonics in which microcavities exhibiting strong exciton–photon interaction may serve as building blocks of optical spiking neurons. The experimental results demonstrate the intrinsic property of exciton–polaritons to resemble the Leaky Integrate‐and‐Fire (LIF) spiking mechanism. It is shown that exciton–polariton microcavities when non‐resonantly pumped with a pulsed laser exhibit leaky integration due to relaxation of the excitonic reservoir, threshold‐and‐fire mechanism due to transition to Bose–Einstein Condensate (BEC), and resetting due to stimulated emission of photons. These effects, evidenced in photoluminescence characteristics, arise within sub‐ns timescales. The presented approach provides means for ultrafast processing of spike‐like laser pulses with energy efficiency at the level below 1 pJ per spike. Abstract : This paper introduces a new approach to neuromorphic photonics which employs the dynamics of strong exciton–photon interaction to imitate the fundamental biological neurons functionality, ‐ the Leaky Integrate‐and‐Fire (LIF) mechanism. Such systems can work as building blocks of optical spiking neurons providing three orders higher processing speed and one order higher energy efficiency in comparison to electronic solutions.